Towards integrated modelling: full image simulations for WEAVE - Dalton, G; Ham, S; Trager, S; Abrams, D; Bonifacio, P; Aguerri, J; Middleton, K; Benn, C; Rogers, K; Stuik, R; Carrasco, E; Vallenari, A; et al. (Society of Photo-optical Instrumentation Engineers, 2016)
We present an integrated end-end simulation of the spectral images that will be obtained by the weave spectrograph, which aims to include full modelling of all effects from the top of the atmosphere to the detector. These data are based in input spectra from a combination of library spectra and synthetic models, and will be used to provide inputs for an endend test of the full weave data pipeline and archive systems, prior to 1st light of the instrument.